Core–shell anatase anode materials for sodium-ion batteries: the impact of oxygen vacancies and nitrogen-doped carbon coating - Bai, Yu-Lin; Xarapatgvl, Raxidin; Wu, Xue-Yan; Liu, Xin; Liu, Yu-Si; Wang, Kai-Xue; Chen, Jie-Sheng (Nanoscale, 2019)
In this work, the impact of oxygen vacancies and nitrogen-doped carbon coating on the sodium-ion storage properties of anatase TiO 2 has been demonstrated. Oxygen vacancies and nitrogen-doped carbon coating were introduced simultaneously by the calcination of core–shell structured TiO 2 spheres in a reducing atmosphere. Compared to the anatase TiO 2 with and without oxygen vacancies, TiO 2−x @NC exhibits much better electrochemical performance in the storage of sodium ions. A high reversible capacity of 245.6 mA h g −1 is maintained at 0.1 A g −1 after 200 cycles, and a high specific capacity of 155.6 mA h g −1 is achieved at a high rate of 5.0 A g −1 . The significantly improved electrochemical performance of the core–shell structured anatase TiO 2 spheres is attributed to the synergistic effect of the oxygen vacancies in the anatase lattice and surface nitrogen-doped carbon coating. This work provides an efficient strategy for improving the electrochemical performance of metal–oxide-based electrode materials for sodium-ion batteries.